Experimental Study for Ability to Use Plaster of Pairs Instead of Normal Concrete - Tariq Hashim, Hashim; Mohammed Mosleh Salman, Dr. (International Journal of Engineering and Technology, 2018)
This research investigated the possibility of using plaster of Paris instead of cement in some internal structural parts and non-exposed to moisture by casting (nine) samples divided in three group. First group was normal concrete, second was plaster of pairs concrete group and finally plaster of Paris with aggregate concrete. All of them have the same dimension (1000×150×200) mm and the same reinforcement ratio. Group one was cured with water while the rest were isolated in a place far away from the moisture. All sample designed to be failed in flexural. The process of testing was divided in two methods; for properties of material used as explain above and for samples tested under two-point load at several curing time (7,28 and 90) days.  Each period consists of three samples one from each group. The result showed that the third group (plaster of Paris with aggregate concrete) approximately closer to normal concrete in applying a load by the ratio of (98%) in 7 days, (87%) in 28 days and (94%) in 90 days. While the second group (plaster of pairs concrete) was acceptable when compared with normal concrete because of missing aggregate.